Effect of mixing sequence on the curing of amine-hardened epoxy/ alumina nanocomposites as assessed by optical refractometry (eXPRESS Polymer Letters, 2008)
High performance refractometry has been proven to be a useful tool to elucidate the isothermal curing process of nanocomposites. As a model system an amine-hardening epoxy filled with non-surface-treated alumina nanoparticles was selected. The tremendous resolution of this experimental technique is used to study morphological changes within nanocomposites via the refractive index. It is shown that these morphological changes are not simply due to the curing process but also depend on the sequence of mixing the nanoparticles either first into the resin or first into the hardener. Independent of the resin/hardener composition, the type of the mixing sequence discriminates systematically between two distinct refractive index curves produced by the curing process. The difference between the two refractive index curves increases monotonically with curing time, which underlines the importance of the initial molecular environment of the nanoparticles.